Dividend Policy As A Moderator of The Effect of Liquidity and Leverage on Firm Value - Sianggi Narina Sukmajaya; Dewa Gede Wirama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Firm value refers to the price a prospective buyer is willing to pay if the company were to be sold. It serves as an economic metric to assess the overall financial position of a company, reflecting how valuable the firm is in terms of its assets, earnings, growth potential, and other relevant factors. This study aims to analyze dividend policy as a moderating variable in the relationship between liquidity, leverage, and firm value among organizations listed on the Indonesia Stock Exchange (IDX) in 2023. The data employed in this study is secondary information sourced from annual financial reviews published through the reliable IDX website or the companies’ individual websites. Liquidity is estimated using the current ratio, leverage is estimated using the debt-to-equity ratio, firm value is calculated using the price-to-book value, and dividend policy is calculated using the dividend payout ratio. The sample consists of 248 companies, selected using the Slovin sampling technique. The findings reveal that liquidity and leverage have no impact on firm value. Dividend policy does not slight the impact of liquidity on firm value. However, dividend policy does moderate the effect of leverage on firm value.